Development of an in situ high-temperature X-ray diffraction technique for lithium-ion battery materials. Issue 76 (3rd September 2021) - Mukai, Kazuhiko; Uyama, Takeshi; Nonaka, Takamasa
Abstract : The development of an in situ high-temperature X-ray diffraction technique for lithium-ion battery materials is crucial for understanding the detailed mechanism of thermal runaway. Abstract : The development of an in situ high-temperature X-ray diffraction technique for lithium-ion battery materials is crucial for understanding the detailed mechanism of thermal runaway. We realized such a technique and employed it on a C6 Li x electrode with an LiPF6 -based electrolyte, thereby revealing multiple transformations through several intermediate stages, i.e., C6 Li → C12 Li → C18 Li/C24 Li → C36 Li → C6, which could be helpful to improve the thermal stability.